2017
DOI: 10.1200/jco.2017.35.15_suppl.e21606
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between statins and breast cancer prognosis varies by statin type and exposure time: A meta-analysis.

Abstract: e21606 Background:Breast cancer is the most common cancer in females. The effects of statins on breast cancer prognosis have long been controversial, so it is important to investigate the relationship between statin type, exposure time, and breast cancer prognosis. This study sought to explore the effect of statins on breast cancer prognosis. Methods:We searched the MEDLINE, EMBASE, Cochrane Library between October 15, 2016 and January 20, 2017. Searches combined the terms “breast neoplasms[MeSH]”, “statins”,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 0 publications
2
29
1
Order By: Relevance
“…A systematic review and meta‐analysis reported a summary relative risk associating statin use with breast cancer recurrence of 0.64 (95% CI: (0.53–0.79) . Another meta‐analysis showed that statin use was associated with lower breast cancer‐specific mortality (lipophilic statins) and all‐cause mortality (lipophilic and hydrophilic statins) . A third meta‐analysis of observational studies showed that postdiagnostic statin use was associated with lower cancer‐specific mortality in breast cancer, and prediagnostic statin use was negatively associated with both all‐cause and cancer‐specific mortality .…”
Section: Statins and Breast Cancer Prognosismentioning
confidence: 99%
“…A systematic review and meta‐analysis reported a summary relative risk associating statin use with breast cancer recurrence of 0.64 (95% CI: (0.53–0.79) . Another meta‐analysis showed that statin use was associated with lower breast cancer‐specific mortality (lipophilic statins) and all‐cause mortality (lipophilic and hydrophilic statins) . A third meta‐analysis of observational studies showed that postdiagnostic statin use was associated with lower cancer‐specific mortality in breast cancer, and prediagnostic statin use was negatively associated with both all‐cause and cancer‐specific mortality .…”
Section: Statins and Breast Cancer Prognosismentioning
confidence: 99%
“…Recent studies demonstrated that stains usage reduces breast cancer-specific mortality in patients with breast cancer. 33,34 Kotamraju et al 35 reported that statins activate arginase-dependent pathways to cause cell death in breast cancer cells. Induction of oxidative stress, 36 stimulation of inducible nitric oxide synthase (iNOS) 35 or alterations of Bax and Bcl-2 levels 37 has been explored as a possible cause of statins' cytotoxicity in MCF-7 breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…For inpatients, statin administration was documented in the charts within 24 h. Statins cause both acute and chronic changes in metabolism, inflammatory state, and vascular morphology. Studies have shown that many effects of statins last more than 2 days after discontinuation, however, some acute effects of statins may be mitigated by missing a dose [24]. This may introduce some bias, however, any effect introduced by 'wearing away' of some therapeutic effect of statins should drive the results towards null hypothesis, and therefore it should not affect the conclusions derived from this study.…”
Section: Discussionmentioning
confidence: 94%